Mapping Prior Knowledge Middle Students in Solving Arithmatics Problems - Khashlati Hilyatul Ajda; Heri Purnomo; Anita Adinda; Zulhamdi Zulhamdi (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2022)
This study aims to determine the effect of prior knowledge in solving arithmetic problems and to describe the mapping of middle students' prior knowledge in solving arithmetic problems. The method used in this study is a mixed method. A total of 63 students of MTsN Batu Malang were involved in this study. The subjects used in this study were 2 students. Both students were selected based on their ability to provide written and oral answers. The instruments used in data collection were a prior knowledge diagnostic test and an arithmetic problem-solving test. The results of this study indicate that prior knowledge affects students' problem-solving abilities, and prior knowledge is needed to solve arithmetic problems, but the low problem-solving test scores are caused by a lack of initial knowledge and also students' understanding of the problems given. The implication of this research is that educators can get an idea of how to map students' prior knowledge. In addition, educators can also design an arithmetic problem learning program design in accordance with the description of students' students' prior knowledge.